Vereinbarkeit von Familie und Beruf: Umfrage unter Radiologen und medizinisch-technischen Angestellten in Kliniken unterschiedlicher Ausrichtung - Schwarz-Bundy, Bogáta D.; Bellemann, Nadine; Heye, Tobias; Radeleff, Boris; Grenacher, Lars; Kauczor, Hans-Ulrich; Weber, Marc-André (Der Radiologe, 2012)
PurposeThe compatibility of family and profession is especially difficult for employees in medical professions because of shift work and overtime. It seems that in the future women are going to represent the majority of medical professionals in Germany. Hence, with the forthcoming lack of physicians in Germany social aspects will also play a greater role in the choice of the place of employment. Therefore a statistical survey was made among employees on how they judge the compatibility of family and job and what they would like to improve.Materials and methodsFrom autumn 2009 until spring 2010 a total of 115 questionnaires were distributed to 8 different academic radiology departments. The anonymous questionnaire with partially open, partially graded questions and partially multiple answer questions was designed with the help of an expert for statistics and analytics and included questions about the employment and family situation, plans for the future, requested flexible working hours and childcare models, as well as ideas for improvement. Of the questionnaires 87 were analyzed with a specially designed access database using, for example descriptive statistics and histogram analyses.ResultsOf the interviewees 68% were female and 31% were male (1% not significant n.s.), 46% had children and 49% were childless (5% n.s.), 63% were medical doctors, 33% radiographers (3% other) and 82% worked full-time. Of the male respondents with children 42% indicated that their spouse was at home, 18% of female respondents with children indicated that their spouse was at home and only mothers worked part-time. Of the male respondents 73% would like to take parental leave, 44% of all respondents (70% of the male respondents and 34% of the female respondents) agreed that radiology is more compatible with family than other medical disciplines and 87% would like to have a childcare possibility in close proximity to the working place.Discussion/conclusionsIn most of the families the classic role model prevails, although women are well-educated and men also set a high value on the compatibility of family and profession and would like to take parental leave and work flexible working hours. This is a chance especially for radiology.
First online: 01 March 2012
Gesehen am 18.06.2018